The Effects of NGOs on Socio-Economic Empowerment of Women: Empirical Evidence from Some NGOs Operating in Ethiopia (Global Journal of Management and Business Research, 2019)
Women have been the most disadvantaged and discriminated sections of society all over the world, particularly in developing countries. This study aimed to investigate the effects of NGOs on socio-economic empowerment of women by conceptualizing and developing five basic dimensions of empowerment including income, saving, decision-making ability, expenditure level, and assets ownership rights of women. To test the hypotheses in this paper the researcher targeted three NGOs operating in the study area for a long period. For analysis data were collected from 80 respondents selected by stratified random sampling technique. Data were analyzed using SPSS V20. The result of the five hypotheses tested indicated the existence of a positive and significant statistical difference between prior and post involvement of women in the various intervention approaches used by the NGOs to empower women the socio-economic perspectives.
Keywords: poverty; empowerment; and NGOS